'Ladd traps' as a visual trap for male and female Queensland fruit fly, Bactrocera tryoni (Diptera: Tephritidae). Issue 3 (9th March 2016) - Schutze, Mark K; W Cribb, Bronwen; Cunningham, J Paul; Newman, Jaye; Peek, Thelma; Clarke, Anthony R
Abstract: Bactrocera tryoni (Froggatt) is Australia's major horticultural insect pest, yet monitoring females remains logistically difficult. We trialled the 'Ladd trap' as a potential female surveillance or monitoring tool. This trap design is used to trap and monitor fruit flies in countries other (e.g. USA) than Australia. The Ladd trap consists of a flat yellow panel (a traditional 'sticky trap'), with a three dimensional red sphere (= a fruit mimic) attached in the middle. We confirmed, in field‐cage trials, that the combination of yellow panel and red sphere was more attractive to B. tryoni than the two components in isolation. In a second set of field‐cage trials, we showed that it was the red‐yellow contrast, rather than the three dimensional effect, which was responsible for the trap's effectiveness, with B. tryoni equally attracted to a Ladd trap as to a two‐dimensional yellow panel with a circular red centre. The sex ratio of catches was approximately even in the field‐cage trials. In field trials, we tested the traditional red‐sphere Ladd trap against traps for which the sphere was painted blue, black or yellow. The colour of sphere did not significantly influence trap efficiency in these trials, despite the fact the yellow‐panel/yellow‐sphere presented no colour contrast to the flies. In 6 weeks of field trials, over 1500 flies were caught, almost exactly two‐thirds of them being females. Overall, flies were more likely to be caught on the yellow panel than the sphere; but, for the commercial Ladd trap, proportionally more females were caught on the red sphere versus the yellow panel than would be predicted based on relative surface area of each component, a result also seen the field‐cage trial. We determined that no modification of the trap was more effective than the commercially available Ladd trap and so consider that product suitable for more extensive field testing as a B. tryoni research and monitoring tool.